Efforts to Increase The Activity Students through Example Non Example Models In Thematic Learning in SD N 1 Karangmalang - Rumanti, Rumanti (Universitas Sebelas Maret, 2020)
The purpose of this study is an effort to increase the activeness of students with the example non example learning model in class 1 thematic learning theme 3 sub-theme 1 morning activities. This research was conducted through a cycle assessment process consisting of four stages, namely: planning, implementing, observing, and reflecting in three cycles of improvement. The conclusions obtained from this study are: (1) Thematic learning with theme 3 sub-themes 1 morning activities using the example non example model can increase the activity and learning outcomes of students. This can be seen from the activeness of students before and after the implementation of the example non example learning model in learning. In the first cycle showed active learning (55%) and learning outcomes (61%). In Cycle II it was able to increase learning activeness (79%) and learning outcomes (85%). In Cycle III was able to increase learning activeness (96%) and learning outcomes (94%).